THE EFFECTIVENESS OF THE PBL MODEL ASSISTED BY ANIMATED VIDEOS IN ENHANCING STUDENTS' CRITICAL THINKING SKILLS - Widiya Rahmawati (Jurnal Profesi Keguruan, 2024)
Seeing the learning conditions in class XI BDP SMK Negeri 1 Slawi has not implemented the PBL model optimally and does not involve student activities. When learning takes place, it is still centered on the teacher and students tend to be passive. This has an impact on the lack of development of student's critical thinking skills during learning. The purpose of this study was to test and analyze the effectiveness of the application of the problem-based learning model assisted by animated videos in improving students' critical thinking skills. The research method used was a quasi-experiment with a nonequivalent control group design. The population of this study was students of class XI BDP SMK Negeri 1 Slawi. The sample of this study was students of class XI BDP 2 as the control class and class XI BDP 4 as the experimental class using purposive sampling techniques. Data collection techniques were tests, observations, interviews, and questionnaires. Data analysis techniques used independent samples t-test and n-gain tests with SPSS Statistic 25 software. The results of the independent samples test showed a sig. (2-tailed) value of 0.042 <0.05 meaning Ha was accepted. So, there is a difference in the average results between the experimental class and the control class. Based on the research results, it can be concluded that the application of the problem-based learning model assisted by animated videos is effective in improving students' critical thinking skills.